Exploring the Cultural Influences on Modern Chinese Jewellery - Yu, Boya; Hashim, Hema Zulaika (Journal of Ecohumanism, 2024)
Since the turn of the twenty-first century jewellery industry of China has been showing clear signs of rapid expansion. A major contributing factor to this development has been the artistic skills of the Chinese designers who have created a separate brand for themselves globally. This paper seeks to understand the rising popularity of the designers in the light of the debate that exists in jewellery designing research field- skill vs aesthetics. The youthful Chinese brand has created a syncretistic design that showcases the traditional Chinese aesthetic (or philosophy) and tempers it with the technical skills of the West. This has led to a new phenomenon of Zhong- reviving the traditional Chinese in the light of the global West. In light of this development, young consumers who have dispensable income in their hand are now bent on purchasing customised bespoke jewellery. Various Chinese designer-artists and their aesthetic branding has been compiled together through various secondary literature review to critically analyse this new Chinese phenomenon visible in the global jewellery market.